Exploring the Impact of E-Recruitment on the Performance of Human Resource Departments in Multinational Organizations (The International Journal for Scientific Research, 2024)
The human resource department is among the crucial units in organizations. Through the department, companies conduct recruitment and selection processes to ensure that they hire people with appropriate skills and other attributes to fit in workplace cultures. The study reviews the effects of e-recruitment on the performance of human resource units in multinational companies. Due to the rising utilization of modern technologies in organizational processes, e-recruitment has emerged as a way of using the Internet to identify suitable individuals to fill vacancies in companies. The benefits associated with e-recruitment include access to many candidates from different parts of the world, convenient communication between the company and job applicants, and lower advertising and information-sharing costs. The literature review in the report also indicates that recruitment processes in multinational companies transformed in recent years. The firms mostly use e-recruitment approaches to reach a large pool of candidates since attracting talent and persuading individuals to work in foreign countries can be challenging. The research will be based on surveys and experimental methods using questionnaires as data collection tools. The findings will illustrate the importance of e-recruitment in improving human resource departments’ capacity to select suitable candidates and reduce labour costs.
Keywords: Multinationals; E-Recruitment; Technology; Candidates